1998
DOI: 10.1007/s004390050897
|View full text |Cite
|
Sign up to set email alerts
|

Complete mutational screening of the CFTR gene in 120 patients with pulmonary disease

Abstract: In order to determine the possible role of the cystic fibrosis transmembrane regulator (CFTR) gene in pulmonary diseases not due to cystic fibrosis, a complete screening of the CFTR gene was performed in 120 Italian patients with disseminated bronchiectasis of unknown cause (DBE), chronic bronchitis (CB), pulmonary emphysema (E), lung cancer (LC), sarcoidosis (S) and other forms of pulmonary disease. The 27 exons of the CFTR gene and their intronic flanking regions were analyzed by denaturing gradient gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 22 publications
(22 reference statements)
2
66
0
1
Order By: Relevance
“…An increased incidence of CFTR mutation has been found in bronchiectasis and at least one CFTR mutation was reported in 10% -50% of a series of patients in different studies (Girodon et al 1997;Bombieri et al 1998;Casals et al 2004;King et al 2004). Often in these patients, only one mutation is CF-causing and no particular mutations have been associated only with bronchiectasis.…”
Section: Cftr Mutations and Disseminated Bronchiectasismentioning
confidence: 99%
“…An increased incidence of CFTR mutation has been found in bronchiectasis and at least one CFTR mutation was reported in 10% -50% of a series of patients in different studies (Girodon et al 1997;Bombieri et al 1998;Casals et al 2004;King et al 2004). Often in these patients, only one mutation is CF-causing and no particular mutations have been associated only with bronchiectasis.…”
Section: Cftr Mutations and Disseminated Bronchiectasismentioning
confidence: 99%
“…Previously, we and others reported a relatively high frequency of R75Q among patients with congenital absence of the vas deferens (CAVD), 10,17,18 bronchiectasis, 7,19 atypical mild cystic fibrosis, 20 chronic idiopathic pancreatitis, 21 allergic bronchopulmonary aspergillosis, 22 and sarcoidosis. 7,8 Bombieri et al concluded from their study that R75Q may be a CFTR gene mutation characteristic of sarcoidosis. 8 Our results do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 88%
“…Two successive studies from Italy reported a high frequency of CFTR mutations in individuals suffering from sarcoidosis. 7,8 The most frequent CFTR mutation was R75Q, which was present in three of 26 cases. 8 These findings prompted us to screen the panel of 63 families with two or more patients for R75Q.…”
Section: Introductionmentioning
confidence: 99%
“…6 During a CFTR gene mutation screening in pulmonary diseases, we previously analysed a group of patients with a variety of obstructive and non-obstructive pulmonary diseases. 7 In that paper, we reported that 5/8 (62%) of sarcoidosis patients had a mutation in the CFTR gene. This high incidence in a limited number of patients prompted us to analyse a second enlarged series of patients to confirm the data.…”
Section: Introductionmentioning
confidence: 95%